The effect of Inoculum to Substrate and Carbon to Nitrogen Ratios on the Biogas Quantity and Quality from Anaerobic Digestion of Salvinia molesta: Experimental and Kinetic Studies - Iqbal Syaichurrozi; M. Fakhri Basyir; Rafi Muhammad Farraz; Putri Kurnia Villta; Nabilah Nabilah; Rusdi Rusdi; Sutaryo Sutaryo (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2022)
The purpose of this study was to investigate the effect of inoculum to substrate (I/S) and carbon to nitrogen (C/N) ratios on the biogas quantity and quality from anaerobic digestion of Salvinia molesta (SM). The I/S was adjusted to become 1.5, 2, 2.5 and the C/N was to become 21.5, 25, 30. Anaerobic digestion (AD) was operated during 30 days under the room pressure and temperature. The results showed that increase in I/S from 1.5 to 2.5 increased the biogas yield from 19.01 to 33.84 mL/g VS. Besides that, it increased the methane content from 52.54 to 69.01%. Furthermore, increase in C/N to 21.5 to 30 decreased the biogas yield from 33.84 to 30.85 mL/g VS and then decreased the methane content from 69.01 to 6.99%. Hence, the best condition was in the substrate with I/S of 2.5 and C/N of 21.5. The measured data was successfully predicted through the modified Gompertz and the first order kinetic models with R2 of 0.9905 and 0.9476 respectively.